Exploring Marketing Strategy for Islamic Boarding Schools in the Minority-Muslim Area of Jembrana Bali - Ahmad Mulhakim; Sigit Priyo Sembodo (The Faculty of Education and Teaching Training, 2022)
The focus of this research (1) is to find out the marketing strategy management and (2) to find the supporting and inhibiting factors of the marketing of Firdaus Islamic Boarding Schools in the Muslim-minority area of ??Jembrana Bali. The qualitative research method used a case study approach—data collection by observation, documentation, and interviews. Data analysis consists of data collection, reduction, display, and conclusion drawing. The research results conclude that: (1) The Marketing Strategy of Islamic Boarding Schools is carried out with three aspects: marketing planning, implementation, and evaluation. Planning is carried out before the distribution activities by involving all internal institutions. Marketing implementation is based on seven aspects: product, price, place, promotion, human resources, infrastructure, and service process. Marketing evaluation is carried out monthly, quarterly, and annually. (2) Supporting factors, namely the location of the cottage, which is in a Muslim minority area, making the institution quickly recognized by the public, the location on the outskirts of the city, and the area of ??the cottage, adequate facilities. There is much support from the Balinese Muslim community and the close ties of tolerance with the non-Muslim Balinese community, the flagship program created. The inhibiting factors are significant competition for Islamic boarding schools (pesantren) in Java and Bali. There is still a public perception that the price to enter the pesantren is expensive, and there are no experts in the field of marketing to manage marketing specifically. Fokus penelitian ini adalah (1) untuk mengetahui manajemen strategi pemasaran dan (2) untuk mengetahui faktor pendukung dan penghambat pemasaran Pondok Pesantren Firdaus di wilayah minoritas Muslim Jembrana Bali. Metode penelitian kualitatif menggunakan pendekatan studi kasus—pengumpulan data melalui observasi, dokumentasi, dan wawancara. Analisis data terdiri dari pengumpulan data, reduksi, display, dan penarikan kesimpulan. Hasil penelitian menyimpulkan bahwa: (1) Strategi Pemasaran Pondok Pesantren dilakukan dengan tiga aspek yaitu perencanaan pemasaran, implementasi, dan evaluasi. Perencanaan dilakukan sebelum kegiatan penyaluran dengan melibatkan seluruh institusi internal. Implementasi pemasaran didasarkan pada tujuh aspek: produk, harga, tempat, promosi, sumber daya manusia, infrastruktur, dan proses layanan. Evaluasi pemasaran dilakukan secara bulanan, triwulanan, dan tahunan. (2) Faktor pendukung yaitu letak pondok yang berada di kawasan minoritas muslim sehingga lembaga cepat dikenal oleh masyarakat, letak di pinggiran kota, dan luas pondok, fasilitas yang memadai. Banyaknya dukungan dari masyarakat muslim Bali dan eratnya ikatan toleransi dengan masyarakat Bali non muslim, program unggulan yang dibuat. Faktor penghambatnya adalah persaingan yang signifikan untuk pesantren di Jawa dan Bali. Masih ada anggapan masyarakat bahwa harga masuk pesantren mahal, dan belum ada ahli di bidang pemasaran untuk mengelola pemasaran secara khusus.